2015
DOI: 10.1111/jwas.12204
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Characterization of Enzymatic Digestion from Fish and Soybean Meal from Simulated Digestive Process of Pacific Bluefin Tuna, Thunnus orientalis

Abstract: The digestive process of the Pacific bluefin tuna (PBT), Thunnus orientalis, was simulated through two phases of in vitro digestion: acidic digestion with porcine pepsin, followed by alkaline digestion with pancreatic crude extract (PCE) obtained from the PBT to hydrolyze fish meal (FM) and soybean meal (SBM) as protein substrates. The crude protein from FM resulted in a lower degree of hydrolysis (73.3%) compared with SBM (79.2%). However, the resulting digested products showed that FM contained 35% more smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Tisochrysis lutea (TIS), Nannochloropsis gaditana (NAN), Tetraselmis suecica (TET), and Scenedesmus almeriensis (SCE). amount of amino acids released and, therefore, this factor could represent a crucial aspect for the bioavailability and further absorption of free amino acids into the enterocytes [48]. Additionally, a linear relationship between CPD and free amino acids released was found for all the microalgae evaluated.…”
Section: Tablementioning
confidence: 81%
“…Tisochrysis lutea (TIS), Nannochloropsis gaditana (NAN), Tetraselmis suecica (TET), and Scenedesmus almeriensis (SCE). amount of amino acids released and, therefore, this factor could represent a crucial aspect for the bioavailability and further absorption of free amino acids into the enterocytes [48]. Additionally, a linear relationship between CPD and free amino acids released was found for all the microalgae evaluated.…”
Section: Tablementioning
confidence: 81%
“…This method employs HPLC columns that separate molecules based on the molecular weight. Only four studies had employed this analytical technique [ 146 , 147 ]. Using this technique, the author showed that in-vitro digestion of soybean minimally increases the low-molecular-weight peptides (<6.5 kDa) compared to fish meal, while similar molecular weight distribution between hydrolyzates of fish meal and poultry meal was observed [ 117 , 118 , 146 , 147 ] .…”
Section: Methodsmentioning
confidence: 99%
“…Only four studies had employed this analytical technique [ 146 , 147 ]. Using this technique, the author showed that in-vitro digestion of soybean minimally increases the low-molecular-weight peptides (<6.5 kDa) compared to fish meal, while similar molecular weight distribution between hydrolyzates of fish meal and poultry meal was observed [ 117 , 118 , 146 , 147 ] . In-vitro digestion of single-cell protein using rainbow trout digestive enzymes yielded two times higher of products with molecular weight between 250 and 4000 Da compared to products with molecular weight less than 250 Da.…”
Section: Methodsmentioning
confidence: 99%
“…The molecular weight distribution (MW) of the CH and FH peptides was determined by Size exclusion chromatography (SEC) using a Varian HPLC system equipped with a diode array detector (DAD) (Varian ™ ProStar) and Galaxy ™ software (Varian, version 1.9.302.952) following the methodology used by Román-Gavilanes et al [39]. 20 µL of the sample was injected at a concentration of 5 mg/ mL.…”
Section: Size Exclusion Chromatography (Sec)mentioning
confidence: 99%
“…The SEC process is based on the fractionation of peptides according to the retention time of the molecules in the particles of the stationary phases, in which the molecules separate from each other according to their molecular size [39]. The distribution of the MW of the CH and FH obtained with the proteases of BP and BK, are shown in Figs.…”
Section: Distribution Of Molecular Weights (Mw) Of Peptides From Hydrmentioning
confidence: 99%